Differential requirements for Gli2 and Gli3 in the regional specification of the mouse hypothalamus - Haddad-Tóvolli, Roberta; Paul, Fabian A.; Zhang, Yuanfeng; Zhou, Xunlei; Theil, Thomas; Puelles, Luis; Blaess, Sandra; Alvarez-Bolado, Gonzalo (Frontiers in Neuroanatomy, 2015)
Secreted protein Sonic hedgehog (Shh) ventralizes the neural tube by modulating the crucial balance between activating and repressing functions (GliA, GliR) of transcription factors Gli2 and Gli3. This balance—the Shh-Gli code—is species- and context-dependent and has been elucidated for the mouse spinal cord. The hypothalamus, a forebrain region regulating vital functions like homeostasis and hormone secretion, shows dynamic and intricate Shh expression as well as complex regional differentiation. Here we asked if particular combinations of Gli2 and Gli3 and of GliA and GliR functions contribute to the variety of hypothalamic regions, i.e., we wanted to approach the question of a possible hypothalamic version of the Shh-Gli code. Based on mouse mutant analysis, we show that: (1) hypothalamic regional heterogeneity is based in part on differentially stringent requirements for Gli2 or Gli3; (2) another source of diversity are differential requirements for Shh of neural vs. non-neural origin; (3) the medial progenitor domain known to depend on Gli2 for its development generates several essential hypothalamic nuclei plus the pituitary and median eminence; (4) the suppression of Gli3R by neural and non-neural Shh is essential for hypothalamic specification. Finally, we have mapped our results on a recent model which considers the hypothalamus as a transverse region with alar and basal portions. Our data confirm the model and are explained by it.